Ngeroncongi And Ngepop : A Study Of Popular Song's Vocal Performance In Keroncong Music In Semarang (Universitas Negeri Semarang, 2021)
Keroncong Music is a music that has different character from other musics, including several techniques in vocal performance, such as luk, nggandul, embat, gregeland cengkok. Nowadays keroncong music does not only perform keroncong songs but also performs popular songs accompanied by keroncong music. When performing popular songs accompanied by keroncong music, usually the performance of each singer will be different. This study aims to determine how the vocal performance of popular songs in keroncong music. The research method used was qualitative. Data collection techniques used observation, interviews, and document study. The results showed that in performing pop songs with a slow tempo accompanied by keroncong music, the techniques used by keroncong singers tended to be Ngeroncongiwhich means that singers still use some keroncong singing techniques such as luk, nggandul, embat, gregel, and cengkokalthough the songs performed have pop genre. Whereas in performing pop songs in fast tempo that are accompanied by keroncong music, the techniques used by keroncong singers tend to pop (ngepop), which means the singers still show pop techniques and improvisation.